Pengaruh Lelang Agunan Terhadap Tingkat Pembiayaan Bermasalah di Bank BJB Syariah - 10010321030, Saefullah Yusuf; Yayat Rahmat Hidayat; Eva Misfah Bayuni (Bandung Conference Series: Syariah Banking, 2025)
Abstract. The issue of non-performing financing (NPF) is a major challenge in Islamic banking risk management because it can increase the potential for losses. One solution is collateral auctions, which involve the sale of collateral assets to cover customer liabilities. This study aims to analyze the effect of the frequency and value of collateral auctions on the NPF level at Bank BJB Syariah for the 2014–2024 period. The method used was quantitative, with simple linear regression analysis using EViews 12 software, using secondary data from auction realization reports and the annual NPF ratio. The results indicate that collateral auctions have a significant and negative effect on non-performing financing, with every 1% increase in auction implementation reducing the NPF ratio by 0.234%. These findings are expected to provide strategic recommendations for Islamic banks in managing financing risk by optimizing the auction process and serve as a basis for developing policies for resolving non-performing financing that are efficient and in accordance with Sharia principles. Abstrak. Permasalahan pembiayaan bermasalah (Non-Performing Financing/NPF) merupakan tantangan utama dalam manajemen risiko perbankan syariah karena dapat meningkatkan potensi kerugian. Salah satu solusi yang digunakan adalah lelang agunan, yaitu penjualan aset jaminan untuk menutup kewajiban nasabah. Penelitian ini bertujuan menganalisis pengaruh frekuensi dan nilai lelang agunan terhadap tingkat NPF di Bank BJB Syariah periode 2014–2024. Metode yang digunakan adalah kuantitatif dengan analisis regresi linier sederhana melalui software EViews 12, menggunakan data sekunder dari laporan realisasi lelang dan rasio NPF tahunan. Hasil penelitian menunjukkan bahwa lelang agunan berpengaruh signifikan dan negatif terhadap pembiayaan bermasalah, dengan setiap kenaikan 1% pelaksanaan lelang dapat menurunkan rasio NPF sebesar 0,234%. Temuan ini diharapkan dapat menjadi rekomendasi strategis bagi bank syariah dalam mengelola risiko pembiayaan melalui optimalisasi proses lelang, serta menjadi dasar dalam penyusunan kebijakan penyelesaian pembiayaan bermasalah yang efisien dan sesuai prinsip syariah.